MEMBANGUN TEORI KONSUMSI ISLAMI MELALUI MODEL INFAK - Anas, Ahmad; Ummah, Afaful (Universitas Muhammadiyah Surabaya, 2020)
This study was based on the assumption that Islamic concumption theory which existstoday is result from combination between conventional concumption theory and Islamicreligion theory. Conventional concumption theory has many limitations and incompatibilitywith Islamic teachings and ethics concumption. This study aims to build Islamic concumptiontheory through infak model. Infak model which is not only materialist, but shar'i, spiritualist,socialist, fair, moral and ethical is believed to be very compatible with the characteristics ofMuslim consumers. This study is a type of library study that requires philosophical andtheoretical studies that have to do with empirical facts. Results of study showed that Infak ofconsumption is an activity to spend wealth in an effort to fulfil the needs for the benefit of theworld and the hereafter. In infak of concumption activities, consumers must pay attention tolimitations that cover two important components, namely Islamic law and ethics. Then infakmodel explains the level of priority that is the theory of consumer decision making inspending wealth. Furthermore, the purpose of consumption in infak of consumption includestwo components; material satisfaction and prosperity in hereafter. Both components arecontained in a term called